2014
DOI: 10.1186/1475-9276-13-16
|View full text |Cite
|
Sign up to set email alerts
|

The role of communication inequality in mediating the impacts of socioecological and socioeconomic disparities on HIV/AIDS knowledge and risk perception

Abstract: IntroductionAlthough the link between social factors and health-related outcomes has long been widely acknowledged, the mechanisms characterizing this link are relatively less known and remain a subject of continued investigation across disciplines. In this study, drawing on the structural influence model of health communication, the hypothesis that differences in concern about and information needs on HIV/AIDS, HIV/AIDS-related media use, and perceived salience of HIV/AIDS-related information, characterized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…While the benefits seem to be generally higher among younger, better educated, and the White racial/ethnic groups, the harms seem to be higher among older, less educated, and minority racial/ethnic groups. These findings are consistent with a growing body of literature on the link between communication inequalities and health that shows that health outcomes could vary across socioeconomic and racial/ethnic population subgroups as a result of differences in motivation for, access to, and use of communication resources (Bekalu & Eggermont, 2014;Viswanath & Emmons, 2006;Viswanath, Ramanadhan, & Kontos, 2007). Overall, the findings of this study highlight the importance of considering users' routine use of social media vis-àvis their emotional connection to such use in describing the link between social media use and health.…”
Section: Discussionsupporting
confidence: 89%
“…While the benefits seem to be generally higher among younger, better educated, and the White racial/ethnic groups, the harms seem to be higher among older, less educated, and minority racial/ethnic groups. These findings are consistent with a growing body of literature on the link between communication inequalities and health that shows that health outcomes could vary across socioeconomic and racial/ethnic population subgroups as a result of differences in motivation for, access to, and use of communication resources (Bekalu & Eggermont, 2014;Viswanath & Emmons, 2006;Viswanath, Ramanadhan, & Kontos, 2007). Overall, the findings of this study highlight the importance of considering users' routine use of social media vis-àvis their emotional connection to such use in describing the link between social media use and health.…”
Section: Discussionsupporting
confidence: 89%
“…The spirituality context emphasized the link between spirituality and health and pointed to the importance of religious leaders and traditional healers . Health communication research on HIV/AIDS has taken up some of these considerations (e.g., Bekalu & Eggermont, 2014;Uwah, 2014). For example, studies have considered cultural contexts (e.g., Basu & Dutta, 2009), economic contexts (e.g., Dasgupta, 2013), gender relations (Dako-Gyeke, 2013), and spirituality (e.g., Muturi, 2011).…”
Section: The New Communications Framework For Hiv/aidsmentioning
confidence: 99%
“…The study performed by Mou and Lin (2014) showed that the daily frequency of respondents browsing general information on the Internet is positively correlated to their food safety risk perception. Bekalu and Eggermont (2014) found that the frequency of respondents' exposure to acquired immunodeficiency syndrome (AIDS)-related content in the media was positively related with their health risk perception level . A study conducted by Dong, Hu, and Zhu (2018) revealed that the respondents' trust towards media information sources was significantly positively related with their environmental risk perception.…”
Section: Introductionmentioning
confidence: 99%
“…First, researchers often focus on only a single aspect of media consumption. For example, Mou and Lin (2014) assessed the frequency of viewing general media content; Bekalu and Eggermont (2014) focused on the frequency of viewing specific risk events in the media; and Dong, Hu, and Zhu (2018) discussed media source credibility (MSC) . Few studies have systematically and comprehensively evaluated media consumption.…”
Section: Introductionmentioning
confidence: 99%